An impedance spectroscopy study on the mitigation of clay slime coatings on chalcocite by electrolytes. (February 2017) - Zhao, Shengli; Guo, Bao; Peng, Yongjun; Mai, Yuliang
Highlights: Changes of electrochemical impedance spectroscopy (EIS) can reflect the slime coating on the particle surface. The impedance was lower in saline water than in DI water indicating that the electrolyte mitigated slime coating. Anions and cations with a greater atomic size yield a lower impedance indicating less slime coating. Abstract: The flotation practice and the previous studies have demonstrated that chalcocite flotation can be depressed by the slime coating of clay minerals (Peng and Zhao, 2011; Zhao and Peng, 2012). In this study, how kaolinite coats chalcocite surface and how electrolytes mitigate this coating were studied using electrochemical impedance spectroscopy (EIS) for the first time. It was found that the formation of kaolinite coating on chalcocite surface decreased the dielectric constant and increased the impedance of chalcocite. Therefore, a reduction in impedance of a clay-coated mineral surface reflects the mitigation of the slime coating. It was also found that kaolinite coated the oxidized chalcocite surface corresponding to the depressed chalcocite flotation in the presence of kaolinite. Electrolytes reduced the electrostatic attraction between kaolinite and chalcocite, resulting in the mitigation of kaolinite coating in saline water and improved chalcocite flotation. For the cations (Li +, Na + and K + ) and anions (F −, Cl − and I − ) examined in this study, the larger ions reduced the slime coating more than the smaller ions presumably due to the greater decrease of electrostatic attraction between chalcocite and kaolinite.